Optimizing the DNA Donor Template for Homology-Directed Repair of Double-Strand Breaks - Fei Song; Knut Stieger (Elsevier, 2017)
The CRISPR-Cas (clustered regularly interspaced short palindromic repeats-associated proteins) technology enables rapid and precise genome editing at any desired genomic position in almost all cells and organisms. In this study, we analyzed the impact of different repair templates on the frequency of homology-directed repair (HDR) and non-homologous end joining (NHEJ). We used a stable HEK293 cell line expressing the traffic light reporter (TLR-3) system to quantify HDR and NHEJ events following transfection with Cas9, eight different guide RNAs, and a 1,000 bp donor template generated either as circular plasmid, as linearized plasmid with long 3' or 5' backbone overhang, or as PCR product. The sequence to be corrected was either centrally located (RS55), with a shorter 5' homologous region (RS37), or with a shorter 3' homologous region (RS73). Guide RNAs targeting the transcriptionally active strand (T5, T7) showed significantly higher NHEJ frequencies compared with guide RNAs targeting the transcriptionally inactive strand. HDR activity was highest when using the linearized plasmid with the short 5' backbone overhang and the RS37 design. The results demonstrate the importance of the design of the guide RNA and template DNA on the frequency of DNA repair events and, ultimately, on the outcome of treatment approaches using HDR.